ECONOMIC AND PUBLIC HEALTH EFFECTS OF IMPLEMENTING OIL-FREE TECHNOLOGIES IN THE U.S. FOODSERVICE INDUSTRY - Манько, Юлія (SWorldJournal, 2025)
The article is devoted to the analysis of the economic, social and health consequences of the introduction of oil-free technologies in the US food service. The purpose of the article is to analyze the economic and social and health effects of the introduc